How places offering apprenticeship take part in vocational training in Pécs, Hungary - Kincsei, Valéria Illésné [Verfasser] (My University, 2015)
This contribution analyses the current and future state of apprenticeships as part of the vocational training system with reference to the economic situation in Pécs, Hungary. In this context, the Hungarian Chamber of Industry and Commerce has an important role to play. Finally, the contribution gives an overview of the different measures and counselling programmes offered to assist young people in the process of choosing a career. (BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 3.5.4 Sozialpartner; I 2.2.2 Osteuropa; Berufsausbildung; Sozialpartner; Berufsorientierung; Ungarn